2022
DOI: 10.3390/ijms23158279
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward Room-Temperature Synthesis and Functionalization of Iron-Oxide Nanoparticles

Abstract: Novel magnetic nanohybrids composed of nanomaghemite covered by organic molecules were successfully synthesized at room temperature with different functionalization agents (sodium polystyrene sulfonate, oxalic acid, and cetyltrimethylammonium bromide) in low and high concentrations. Structural, vibrational, morphological, electron energy-loss spectroscopy, magnetic, and Mössbauer characterizations unraveled the presence of mainly cubic inverse spinel maghemite (γ-Fe2O3), whilst X-ray diffraction and 57Fe Mössb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Moreover, all the samples (see zoomed region in Figure 6c), present a very small coercivity field (around 50 Oe) at RT, suggesting that at least parts of the samples are in a superparamagnetic regime in close agreement with functionalized iron oxide nanostructures found in the literature. 41 At 5 K (Figure 6d), all the samples showed an FI character, as would be expected for the cubic spinel structure of the γ-Fe 2 O 3 , also highlighted by Mossbauer spectroscopy. All the M s values estimated from LAS in Figure 6e,f are below the bulk values for the Fe 3 O 4 (92 emu/g) and γ-Fe 2 O 3 (60−80 emu/g).…”
Section: ■ Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…Moreover, all the samples (see zoomed region in Figure 6c), present a very small coercivity field (around 50 Oe) at RT, suggesting that at least parts of the samples are in a superparamagnetic regime in close agreement with functionalized iron oxide nanostructures found in the literature. 41 At 5 K (Figure 6d), all the samples showed an FI character, as would be expected for the cubic spinel structure of the γ-Fe 2 O 3 , also highlighted by Mossbauer spectroscopy. All the M s values estimated from LAS in Figure 6e,f are below the bulk values for the Fe 3 O 4 (92 emu/g) and γ-Fe 2 O 3 (60−80 emu/g).…”
Section: ■ Introductionsupporting
confidence: 70%
“…However, it is important to mention that the M(H) loops for the NPD2 and NPD3 samples do not reach the saturation regime. Moreover, all the samples (see zoomed region in Figure c), present a very small coercivity field (around 50 Oe) at RT, suggesting that at least parts of the samples are in a superparamagnetic regime in close agreement with functionalized iron oxide nanostructures found in the literature . At 5 K (Figure d), all the samples showed an FI character, as would be expected for the cubic spinel structure of the γ-Fe 2 O 3 , also highlighted by Mössbauer spectroscopy.…”
Section: Raman Tem Stem and Saed Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the threshold value depends strongly on the size of the NPs and also the functionalized agent. The latter may give thermal stability to the iron oxide NP sample, i.e., the γ α transition will occur at higher temperatures [ 23 , 24 , 25 , 26 ]. Hence, two protocols given in the experimental sections were performed to correctly analyze the RG1 sample.…”
Section: Resultsmentioning
confidence: 99%